Menanamkan Kesadaran Sanitasi Sejak Dini untuk Penguatan Karakter Siswa Orang Asli Papua (OAP) di Merauke - Sri Ananda Pertiwi; Rawuh Yuda Yuwana; Ferry Irawan (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service program aims to foster sanitation awareness and strengthen character values among elementary school students of the Indigenous Papuan (OAP) community in Merauke, involving 80 students. The implementation method employed socialization and hands-on practice using a participatory approach. The intervention was carried out through daily routines monitored by classroom teachers and supported by visual demonstration-based education, direct practice, and daily agenda books. Evaluation instruments included observation sheets, tests, and interviews, which were analyzed descriptively. The results of this program showed an improvement in students’ understanding of sanitation, categorized as good, with an average score of 80 for the importance of sanitation, 75 for sanitation procedures, and 78 for the impact of sanitation. Furthermore, 81% of students consistently applied daily hygiene practices. Interviews with teachers and the principal confirmed that students had become more disciplined in maintaining personal cleanliness. Overall, this program demonstrated that consistent intervention significantly contributed to improving students’ sanitation awareness and healthy living behaviors.